Ответы и объяснения

  • Участник Знаний
2014-03-16T14:51:43+00:00
(-3;-5)-является
-3·(-5)-(-3)=15+3=18 
(-5;-3)-нет
-5·(-3)-(-5)=15+5=20
(2;10) да
2·10-2=20-2=18
  • Участник Знаний
2014-03-16T14:51:57+00:00
XY - X = 18 
X * ( Y - 1 ) = 18 
=================
( - 3 ; - 5 )
- 3 * ( - 5 - 1 ) = - 3 * ( - 6 ) = 18 
 ЯВЛЯЕТСЯ РЕШЕНИЕМ
==================
( - 5 ; - 3 )
- 5 * ( - 3 - 1 ) = - 5 * ( - 4 ) = 20 
НЕ ЯВЛЯЕТСЯ РЕШЕНИЕМ
=====================
( 2 ; 10 ) 
2 * ( 10 - 1 ) = 2 * 9 = 18 
 ЯВЛЯЕТСЯ РЕШЕНИЕМ